Interest Rates and Unemployment: An Underwhelming Relation - Blair Fix (Economics from the Top Down, 2023)
For the last few months, I've been studying the distributional effects of interest-rate hikes. There's been no shortage of surprising results. In this post, I'll discuss an effect that is surprising because it's underwhelming. Many economist claim that when interest rates rise, unemployment will increase. The idea is that higher rates make businesses tighten their belts, leading to less hiring and greater unemployment. Looking at the evidence, I find that this claim is not particularly compelling.
Keywords: E4; J6; E24; 330; interest rate; unemployment